METABOLIC CHANGES OF SERUM CATHEPSIN D IN PERIODONTITIS WITH AND WITHOUT TYPE 2 DIABETES MELLITUS - D.S.PUSHPARANI; S. NIRMALA (International Journal of Pharma and Bio Sciences, 2014)
Diabetes is shown to have an increased risk for periodontal disease compared to non-diabetes. The present study aimed to evaluate the concentration of serum cathepsin D level in periodontitis subjects with and without type 2 diabetes mellitus. We studied a total of 600 subjects categorized into 4 groups as Group I (150 healthy subjects as control), Group II (150 type 2 diabetes mellitus with periodontitis), Group III (150 type 2 diabetes mellitus without periodontitis) and Group IV (150 non-diabetic patients with periodontitis). Serum concentration of cathepsin D was measured by means of UV absorption spectrophotometer at 280 nm. The activity of cathepsin D was found to be elevated 8 times in non-diabetic periodontitis subjects (group IV) when compared to control and it was 3 times higher when compared to type 2 diabetes mellitus with periodontitis (group III). It gives an evidence for the release of lysosomal enzymes during periodontal tissue damage.